2016
DOI: 10.4149/218_150807n435
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife stereotactic radiosurgery and stereotactic ablative radiation therapy of patients with prostate cancer bone metastases.

Abstract: The aim of the study was to evaluate the effectiveness and toxicity of CyberKnife (CK) stereotactic radiosurgery (SRS) and stereotactic ablative radiation therapy (SABR) of patients with prostate cancer bone metastases. Analysis of prognostic and predictive factors was also performed.Material consisted of 51 patients with 71 bone oligometastases treated using CK SRS/SABR. In half of the patients single lesion was treated, in half 2-5 lesions. Median PSA concentration at the time of metastasis detection was 5.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The exclusion reasons with references are listed in Data S2. Finally, 14 articles were selected for data extraction and subsequent qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The exclusion reasons with references are listed in Data S2. Finally, 14 articles were selected for data extraction and subsequent qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…One randomized controlled trial was found, but it did not meet all the eligibility criteria, so it was not included in the qualitative analysis . Thirteen articles were single‐arm case series/cohort studies, and one case–control series, with five (36%) prospective and nine (64%) retrospective researches . Median follow‐up period varied from 10.2 to 36.6 months (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations